Pengaruh Kualitas Produk Dan Kualitas Layanan Terhadap Niat Pembelian Kembali Melalui Kepuasan Pelanggan Sebagai Pemediasi - Adittia Wicaksono; Putu Yudi Setiawan (Relasi : Jurnal Ekonomi, 2025)
Competition between companies in the insurance sector is very sharp. The consequences of this increasingly sharp competition will give rise to three possibilities facing a company, namely closing its business activities, continuing with the business activities it has carried out, or remaining superior and even growing. The aim of this research is to examine and explain the role of the influence of product quality and service quality on repurchase intentions through customer satisfaction as a mediator at PT Great Eastern General Insurance Household Insurance in Bali. The sampling method used was probability and the proportionate cluster technique. The analysis technique used is Structural Equation Model (SEM) using an analysis tool in the form of SmartPLS 3.2.9 software. The results of the analysis show that product quality and service quality on repurchase intention through customer satisfaction have a positive and significant effect on repurchase intention to repurchase householder insurance. This research provides implications for companies as material for consideration and evaluation in increasing repurchase intentions. Because this can significantly influence customers repurchase intentions with Great Eastern Insurance.